2014
DOI: 10.1371/journal.pone.0102659
|View full text |Cite
|
Sign up to set email alerts
|

Methane Production and Methanogenic Archaea in the Digestive Tracts of Millipedes (Diplopoda)

Abstract: Methane production by intestinal methanogenic Archaea and their community structure were compared among phylogenetic lineages of millipedes. Tropical and temperate millipedes of 35 species and 17 families were investigated. Species that emitted methane were mostly in the juliform orders Julida, Spirobolida, and Spirostreptida. The irregular phylogenetic distribution of methane production correlated with the presence of the methanogen-specific mcrA gene. The study brings the first detailed survey of methanogens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 53 publications
1
26
0
Order By: Relevance
“…Moreover, even though it has been suggested that they could affect plants (Taffner et al, ), which would in turn affect pest insects, there is scant information on their importance and the roles they play in these hosts (Gurung, Wertheim, & Falcao Salles, ). Until very recently, methanogenic and non‐methanogenic Archaea from Phylum Euryarchaeota had only been reported in the hindguts of methane producing arthropods—beetles, cockroaches, termites, and millipedes—where there is limited oxygen availability (Brune, ; Egert et al, ; Hara, Shinzato, Seo, Oshima, & Yamagishi, ; Shinzato, Matsumoto, Yamaoka, Oshima, & Yamagishi, ; Šustr, Chroňáková, Semanová, Tajovský, & Šimek, ; Tinker & Ottesen, ). Nevertheless, a shotgun metagenomic analysis of the gut content of P. xylostella larvae identified Euryarchaeota DNA in very low proportions (Xia et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, even though it has been suggested that they could affect plants (Taffner et al, ), which would in turn affect pest insects, there is scant information on their importance and the roles they play in these hosts (Gurung, Wertheim, & Falcao Salles, ). Until very recently, methanogenic and non‐methanogenic Archaea from Phylum Euryarchaeota had only been reported in the hindguts of methane producing arthropods—beetles, cockroaches, termites, and millipedes—where there is limited oxygen availability (Brune, ; Egert et al, ; Hara, Shinzato, Seo, Oshima, & Yamagishi, ; Shinzato, Matsumoto, Yamaoka, Oshima, & Yamagishi, ; Šustr, Chroňáková, Semanová, Tajovský, & Šimek, ; Tinker & Ottesen, ). Nevertheless, a shotgun metagenomic analysis of the gut content of P. xylostella larvae identified Euryarchaeota DNA in very low proportions (Xia et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the mcrA gene has successfully been applied to monitor methanogens in soil invertebrate guts 43 , 44 . Detection of mcrA genes in starved bivalves suggests that the methane was not produced by ingested microbes.…”
Section: Discussionmentioning
confidence: 99%
“…In insects, methanogenic and non‐methanogenic archaea belonging to the phylum Euryarchaeota, have been reported in beetles, cockroaches, termites, and millipedes. The methanogenic archaea are usually present in the hindguts, an environment with limited oxygen availability (Shinzato et al., ; Hara et al., ; Šustr et al., ; Tinker & Ottesen, ). Ziganshina et al.…”
Section: Archaeamentioning
confidence: 99%